Odour attractants for Glossina pallidipes in south-western Ethiopia - Tikubet, G.; Duffera, W.; Tegene, G.; Leak, S.G.A.; Mulatu, W.; Richardson, T. (ILCA/ILRAD, 1988)
Results of a study conducted to compare the effectiveness of combinations of odour attractants and the Ngn and bicenical traps in the Ghibe river valley, Ethiopia. Includes data on catches of male & female G. pallidipes with bicenical & Ngn traps using acetone & con unine, hoppo dung, pig urine, and 1-octen-3-01.